Interspecies differences in the transcriptome response of corals to acute heat stress - Da-Anoy, Jeric; Posadas, Niño; Conaco, Cecilia (PeerJ, 2024)
Rising sea surface temperatures threaten the survival of corals worldwide, with coral bleaching events becoming more commonplace. However, different coral species are known to exhibit variable levels of susceptibility to thermal stress. To elucidate genetic mechanisms that may underlie these differences, we compared the gene repertoire of four coral species, Favites colemani, Montipora digitata, Acropora digitifera, and Seriatopora caliendrum, that were previously demonstrated to have differing responses to acute thermal stress. We found that more tolerant species, like F. colemani and M. digitata, possess a greater abundance of antioxidant protein families and chaperones. Under acute thermal stress conditions, only S. caliendrum showed a significant bleaching response, which was accompanied by activation of the DNA damage response network and drastic upregulation of stress response genes (SRGs). This suggests that differences in SRG orthologs, as well as the mechanisms that control SRG expression response, contribute to the ability of corals to maintain stability of physiological functions required to survive shifts in seawater temperature.
Keywords: Thermal stress; Adaptation; DNA damage; Seriatopora caliendrum